Peningkatan Akurasi Pengukuran Kadar Gas CO pada Node Sensor Sistem Monitoring Kualitas Udara Menggunakan Kompensasi Kesalahan - Heri Subagiyo; Welliya Randa; Retno Tri Wahyuni; Memen Akbar (Jurnal Elektro dan Mesin Terapan, 2021)
Increasing the accuracy of the MQ-7 sensor node in the air quality monitoring system is a process to get better results from measuring carbon monoxide (CO) gas levels. The stage of increasing this accuracy begins with testing the comparison of data between the measuring instruments designed and the standard operational equipment of the BMKG Meteorological Station Class I Pekanbaru which is used as a benchmark. The purpose of this process is to get the correction value from the sensor output, which will be used as a value in compensating. In this study, there was an increase in the accuracy of measuring instruments by 79.86% from the previous study, from 19.74% to 99.60%. Thus, the increase in the accuracy of the measurement of carbon monoxide (CO) gas levels in the air quality monitoring system has shown better results than previous research.